An organic proton battery employing two redox-active quinones trapped within the nanochannels of zeolite-templated carbon. (October 2016) - Nueangnoraj, Khanin; Tomai, Takaaki; Nishihara, Hirotomo; Kyotani, Takashi; Honma, Itaru
Abstract: For the first time, we present in this work a simple method to achieve high energy density device by functionalizing zeolite-templated carbon (ZTC) with quinone molecules. Two types of quinone, anthraquinone and tetrachlorohydroquinone, which have different redox potential, were introduced into ZTC framework by a wet impregnation method, and were characterized in a sulfuric acid. An organic proton battery was assembled from two different functionalized-ZTC electrodes in the sulfuric acid, where the energy is stored by a proton-rocking-chair mechanism resulting from a quinone couple trapped inside the nanopores of ZTC with a less crystalline or nanocrystalline structure. The assembled device possesses an energy density as high as 30.6 Wh kg −1, which is superior to the activated-carbon-based capacitors working in the organic electrolytes and lead batteries.